Correlation Analysis between Rehabilitation Mechanism of Top Tank Walking and Spinal Stability Training Principle - Hua LI; Xinmiao Yao; Guoqing Zhou (康复学报)
Top tank walking as a form of sports or games, which can strengthen the balance of the body and help prevent and treat spinal diseases. By literature research methods and using the principles of spine kinematics, this paper analyzed the correlation between the rehabilitation mechanism of top tank walking and spinal stability training principle. The study found that top tank walking can mobilize and maintain the relevant muscle groups in the spine posture effectively, affect the deep muscles of the cervical vertebrae, the chest and lumbar muscles, and stimulate the activity of the local stable muscles of the spine; the spine rehabilitation training of using top tank or top tank walking, should based on the fatigue of the patient's muscle contraction, step by step, while paying attention to the principle of specificity and individuality. Top tank walking can be tried clinically as one of the personalized exercise prescriptions for spinal rehabilitation training.